“Explore the entire South East of Russia”: Caucasian travelogues by Stepan Nechaev - V. A. Shkerin (Гуманитарные и юридические исследования)
Stepan D. Nechaev is a poet and prose writer of the first quarter of the 19th century, who is known not so much for his literary works as for his literary connections. He was friends with A. Bestuzhev (Marlinsky), was familiar with K. Ryleev, V. Kyuchelbeker, D. Davydov, N. Polevoy, published in almanacs “Polar Star”, “Mnemosyne”, “Urania”, in the journals “Herald of Europe”, “Moscow Telegraph”, “Well-intentioned”, “Ladies’ Magazine”. Nechaev undertook a long trip around the Caucasus for ethnographic study and literary description of an unfamiliar region in 1823. The result of this trip was two literary travelogues – a large poem “Memories” and prose “Excerpts from travel notes about South-Eastern Russia”. Most of the time the author-traveler spent on the Caucasian Mineral Waters – in Goryachevodsk (future Pyatigorsk) and Kislovodsk. However, the entire Caucasian route turned out to be much longer: through Starocherkassk, Stavropol and Georgievsk to the Caucasian waters and back – through Georgievsk, Mozdok and Kizlyar to Astrakhan and further up the Volga. During this voyage, Nechaev had a number of important meetings. The official and writer V. Timkovsky, who was under General A. Yermolov, may have revealed to Nechaev the secret plans of the environment of the “proconsul of the Caucasus”. The Kabardian educator Sh. Nogmov introduced him to the culture and way of life of his people. A disgraced officer and future participant in the uprising on Senate Square A. Yakubovich became a friend of Nechaev and the hero of one of his poems. Nechaev’s Caucasian travelogues were published in 1825–1826, being one of the last lifetime publications of this author. After the defeat of the Decembrist uprising, among whom were friends and acquaintances of Nechaev (K. Ryleev, A. Bestuzhev, V. Kyuchelbeker, A. Yakubovich), he also came under suspicion. No great fault was found for Nechaev, but he preferred to give up his dream of literary glory